IMPROVING STUDENTS’ LISTENING ABILITY AT ELEVENTH GRADE IN SMA NEGERI 4 PEMATANGSIANTAR THROUGH AUDITORY, INTELLECTUALLY, AND REPETITION (AIR) MODEL - Juni Sari Sianturi; Selviana Napitupulu (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
Listening is one of the essential skills in English language learning; however, many students still face difficulties in comprehending spoken texts, particularly in distinguishing the pronunciation of regular past tense verbs ending in –ed (/t/, /d/, and /ɪd/). This study aimed to examine the effectiveness of the Auditory, Intellectually, and Repetition (AIR) learning model in improving students’ listening ability at the eleventh grade of SMA Negeri 4 Pematangsiantar. This research employed a quantitative approach using a quasi-experimental design. The participants consisted of 72 eleventh-grade students divided into an experimental group (XI-8) and a control group (XI-7). Data were collected through pre-test and post-test listening assessments and analyzed using descriptive statistics and inferential analysis. The findings revealed that the experimental group showed a significant improvement in listening performance, with the mean score increasing from 52.77 in the pre-test to 77.36 in the post-test. Meanwhile, the control group experienced only a slight improvement. The results indicate that the AIR learning model is effective in enhancing students’ listening comprehension, particularly in recognizing the pronunciation of regular past tense verbs ending in –ed. Therefore, the AIR model can be considered an effective alternative strategy for teaching listening in senior high schools. Keywords: Listening ability, AIR learning model, Pronunciation, Regular past tense verbs,Quasi-experimental study.